Diffusion of innovations theory in German physiotherapy - A qualitative study of the innovation-decision-process among German Early Adopters / Diffusionstheorie in der Physiotherapie - Eine qualitative Untersuchung des Innovations-Entscheidungsprozesses bei deutschen «Early Adoptern - Reiter Nils Lennart; Rosen Diane; Vogel Barbara; Höppner Heidi (Sciendo, 2023)
The dissemination of evidence-based practice in German physiotherapy is limited by several barriers. However, a recent study shows that some German physiotherapists are already successfully implementing such a practice. Based on Everett M. Rogers' diffusion of innovations theory, this study defined evidence-based practice as an innovation in German physiotherapy to gain insight into therapists' strategies to overcome these barriers.